Implications of Job Demand - Control Support Models and Protection Motivation Theory against Nurse Compliance - Sakti, Ifa Fannya; Ramadhani, Aulia (International Journal of Psychosocial Rehabilitation, 2020)
Background: Documentation of nursing care is a very important activity for nurses. Nurse compliance in conducting tasks can be influenced by the job characteristics of job demand - control support and protection motivation. Purpose: this study is to analyze the relationship between job demand - control support and protection motivation towards compliance nurses in filling nursing documentation. Method: The study method used was descriptive observational research with cross sectional approach. The population consists of nurses on duty in the inpatient ward of Malang Waluya Hospital. The sampling technique used was simple random sampling with a total sample of 118 nurses. This study used a questionnaire and a complete checklist of nursing care documentation. The time of the study was in October 2019. The statistical test to test the relationship between variables used Chi-Square. Results: showed that there was no significant relationship between job demand - control support (p = 0.456) and protection motivation (p = 0.157) on compliance nurses in filling nursing documentation. Conclusion: this study is the characteristics of job demand - control support and protection motivation do not affect the nurse's compliance because the nurse's compliance behaviour is related to coping decided by the employee. It is recommended that a reward be given for the compliance attitude that has been demonstrated by the nurse.